2001
DOI: 10.1177/00912700122010726
|View full text |Cite
|
Sign up to set email alerts
|

Oral Bioavailability and Disposition of [14C]Omapatrilat in Healthy Subjects

Abstract: The objective of this study was to determine the absolute oral bioavailability and disposition of omapatrilat. This single-dose, randomized, crossover study of 20 mg intravenous and 50 mg oral [14C]omapatrilat was conducted in 12 healthy male subjects to determine the disposition and oral bioavailability of omapatrilat, an orally active vasopeptidase inhibitor. Blood samples were collected up to 120 hours, and the excreta were collected over 168 hours postdose. Plasma concentrations of omapatrilat were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The presence of very little parent compound in the 1-h plasma sample before DTT reduction in all three species suggested that unchanged gemopatrilat was rapidly cleared from the plasma by forming disulfide linkages with cysteine sulfhydryl groups on the protein. This phenomenon has been observed for other sulfhydryl containing compounds like omapatrilat, captopril, and penicillamine (Kripalani et al, 1983;Migdalof et al, 1984;Keire et al, 1993;Iyer et al, 2001;Malhotra et al, 2001). Due to the reversible nature of the disulfide bond in vivo (Gilbert, 1995), the disulfide adducts of gemopatrilat could act as depot for slow release of the drug.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The presence of very little parent compound in the 1-h plasma sample before DTT reduction in all three species suggested that unchanged gemopatrilat was rapidly cleared from the plasma by forming disulfide linkages with cysteine sulfhydryl groups on the protein. This phenomenon has been observed for other sulfhydryl containing compounds like omapatrilat, captopril, and penicillamine (Kripalani et al, 1983;Migdalof et al, 1984;Keire et al, 1993;Iyer et al, 2001;Malhotra et al, 2001). Due to the reversible nature of the disulfide bond in vivo (Gilbert, 1995), the disulfide adducts of gemopatrilat could act as depot for slow release of the drug.…”
Section: Discussionmentioning
confidence: 57%
“…Compounds such as omapatrilat and captopril, which contain a free sulfhydryl group have the propensity to form disulfide linkages with endogenous thiols, including cysteine and the thiols on proteins (Kripalani et al, 1983;Migdalof et al, 1984;Iyer et al, 2001;Malhotra et al, 2001). Approximately half of the drug-related radioactivity in the systemic circulation was present as disulfide forms of gemopatrilat and its sulfhydryl-containing metabolites that was not extractable into organic solvents but could be reduced chemically to gemopatrilat and its sulfhydryl-containing metabolites ex vivo after treatment of plasma with dithiothreitol, a disulfide-reducing agent (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be explained in part by the pharmacokinetics of omapatrilat and its metabolites. Plasma radioactivity after dosing with radiolabeled omapatrilat declines very slowly in healthy subject, with a terminal half-life of about 8 to 9 d and a large steady-state volume of distribution (21 l/kg) suggestive of a deep pharmacokinetic compartment (21). In addition, one of the metabolites of omapatrilat, the L-cysteine mixed disulfide adduct, has a potential to revert to omapatrilat in vivo and therefore prolong its biologic activity (22).…”
Section: Effects Of Omapatrilat On Ace and Nep Inhibitionmentioning
confidence: 99%